Evidence of dependence between the deoxygenation activity and metal-support interface - Abreu Teles, Camila; Duong, Nhung; Rabelo-Neto, Raimundo Crisostomo; Resasco, Daniel; Noronha, Fábio Bellot (Catalysis science & technology, 2022)
The nature of the active sites responsible for the cleavage of C-O bonds in biomass-derived phenolic compounds has been a subject of speculation. Although HDO activity has long been attributed to the combination of the hydrogenation activity of the metal and the dehydration activity of acid sites, recent work has shown that the deoxygenation takes place at the metal-oxophilic site interface. In this work, cleavage of different C-O bonds (hydroxyl and methoxy groups) has been investigated by testing Pt/SiO 2 and Pt/Nb 2 O 5 catalysts for the hydrodeoxygenation of phenol, anisole and guaiacol in the gas phase. Important differences in product distribution were observed depending on the nature of the support. Hydrogenated products were obtained over silica-supported catalysts while niobia promoted the formation of deoxygenated products. By varying the metal loading and particle size, it was found that the length of the Pt-Nb 2 O 5 interfacial perimeter decreases as a function of particle size, along with the deoxygenation rate. A correlation between the interfacial perimeter and HDO activity was demonstrated. From this analysis, it was concluded that HDO is a structure sensitive reaction and the perimeter of the metal-oxophilic site interface is the active site responsible for the deoxygenation reaction. The deoxygenation of lignin-derived compounds occurs in the Pt-NbO x interface, with the HDO rate varying with its perimeter.